IMPLEMENTASI PRODUK SMART CITY MELALUI APLIKASI REAKSI ATAS BERITA WARGA (RABEG) DALAM KETERBUKAAN INFORMASI PUBLIK BERDASARKAN PERATURAN WALIKOTA SERANG NOMOR 36 TAHUN 2018 - Ita Ismawana; Abu Nawas; Agus Prihartono (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Efforts to advance the smart city in Serang City involve all Regional Apparatus Organizations (OPD), with the Serang City Communication and Information Agency (Diskominfo) as the department overseeing the smart city program in Serang City. One of the implementations of the smart city program is the RABEG application. The researcher aims to examine this topic through a study entitled